Rheological behavior of film-forming solutions and film properties from Artemisia sphaerocephala Krasch. gum and purple onion peel extract. (September 2018) - Liang, Tieqiang; Sun, Guohou; Cao, Lele; Li, Jian; Wang, Lijuan
Abstract: The effects of a natural dye extracted from purple onion peel (POPE) on the rheological properties of the film-forming solutions from Artemisia sphaerocephala Krasch. gum (ASKG) were investigated, and the film properties from ASKG and POPE were also tested. The rheological results revealed that ASKG solutions containing POPE formed a weak gel and that POPE interacted with ASKG molecules through hydrogen bonds, altering their network. The addition of POPE decreased the tensile strength, the elongation at fracture, the water vapor permeability and the light transmission rate of the ASKG films, but increased the oxygen permeability from 0.0125 to 0.0170 (cm 3 ∙mm)/(m 2 ∙day∙atm). The POPE solution exhibited a change in color, from pink to orange, when its pH varied in the range 2.0–11.0. In addition, the POPE-containing ASKG films responded to exposure to NH3 as their color changed from brown to brownish red under a certain relative humidity. The results suggest that ASKG could be used as a packaging material and that POPE-containing ASKG films express potential as intelligent packaging materials and gas-sensing labels. Graphical abstract: Image Highlights: An intelligent film from Artemisia sphaerocephala Krasch. gum was prepared. Purple onion peel extract was incorporated into the film as a pH indicator. The rheology of the film-forming solution was investigated. The composite film was sensitive to pH changes. The pH-sensing film could be used to detect NH3 .